Shape development of trondhjemite pebbles and cobbles on shores in the southwestern Finnish Archipelago - Pyökäri, Mauri (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1980)
The morphometry of trondhjemite pebbles and cobbles from till and esker material and from moraine-shore and esker-shore material was studied in the Airisto area, SW Finnish Archipelago. The maximum projection roundness, sphericity, and oblate-prolateness were measured on 2000 pebbles and cobbles in the 16-256 mm size range. Wave energy was low at the study sites, which owing to land uplift rise beyond the reach of littoral forces in a relatively short time (the upper beach over a period of about 800 years). Of the three indices, roundness shows the greatest variation, from 0.30 to 0.72. The oblate-prolate index also showed significant variations (-0.66 - + 1.43). The poorest indicator, but not entirely useless as a discriminatory tool, is the sphericity index, which showed least change (0.69 - 0.78). The increase in roundness and decrease in oblate-prolate index are predominantly the results of abrasion caused by the sliding and rolling of pebbles and cobbles to and fro over sand and gravel in the breaker and swash zones. On mixed gravel-cobble shores from till pebbles (16-64 mm) were most disc-like while cobbles (64-128 mm) were most disc-like on esker shores.